The Development of Learning the Arts of Dance to the Ability of Early Childhood Gross Motor Development - Liya, Apri; Katoningsih, Sri (Early Childhood Research Journal (ECRJ), 2021)
Art is very important in human life, especially for early childhood development. The function of art in education is to develop early childhood development both physically and mentally. Good learning methods are fun and appropriate to the level of children's needs. The learning process seeks to develop the potential for various aspects of development, such as NAM, physical motor, social emotional, cognitive, language, and art. The purpose of this study is to examine literature, articles and research documents that identify the application of dance learning to gross motor skills of early childhood . To develop children's physical motor development, it can be done by using dance learning methods. Learning the art of dance is expressive, creative and imaginative so that it can trigger children's enthusiasm to carry out activities. In addition, learning the art of dance also develops creativity and helps children's physical and spiritual development. Through the basic movements of the dance, the child's gross motor skills will be trained so that the child's development will develop optimally. The research method used was literature review research in the form of scientific articles with a total of approximately 20 articles consisting of 15 national journals and 5 international journals. Results and discussion: this study obtained the results that the application of learning dance to gross motor skills of children obtained positive results due to significant changes. Conclusion: that there is an influence in the development of the art of dance on gross motor skills of early childhood.